Bullying phenomenon in secondary schools: A research prospect / Nur Fakhzan Marwan - Marwan, Nur Fakhzan (2005)
Bullying is a prevailing and perhaps the most under-reported safety problem in either Malaysian schools or elsewhere. Various reports show that bullying has long-lasting harmful effects, for both victims and bullies. However, there has been no specific study that addresses this problem in Malaysia. Therefore, this paper proposes a study that can be undertaken in looking into a deeper insight of bullying problem, which may lead to the design and implementation of prevention and intervention. A modified Peer Relations Assessment Questionnaire (Rigby 1997) will be used to assess perceptions of the nature and extent of student violence, bullying, student engagement in violent behaviour towards peers, and victimisation (from the perspectives of parents, teachers and students). Other constructs central to the study will be measured by researcher-designed (or modified) instruments. Pupils' conduct, performance and school attendance will be measured by teacher ratings.